Video games for increasing middle-aged adults’ English vocabulary and motivation (2023)
Video games are considered relevant digital language learning tools for improving different language skills, particularly vocabulary. Previous studies have investigated video games predominantly with EFL young learners, teenagers and young adults in schools and universities. However, less research has focused on middle-aged EFL learners and their vocabulary increase. Investigating older learners’ vocabulary increase through video games-based learning is important because vocabulary is an essential set of building blocks for communication, and video games can become an adequate learning resource for this underexplored population. The present study, therefore, investigated whether video games are effective digital language learning tools to increase middle-aged learners’ vocabulary and to improve motivation. To do so, a case study was implemented with two beginner-level middle-aged adults to observe the acquisition and improvement of vocabulary when exploring the educational video game “Who is Oscar Lake?”. Data were collected through observations, interviews, questionnaires, and vocabulary tests and lists that both participants completed throughout ten game sessions. Data were analyzed through content analysis. The study revealed enhancement in participants’ vocabulary in the video game context, evident from pre- and post-test comparisons and vocabulary lists. For instance, María's vocabulary about the game increased from 12 to 110. Similarly, Luis increased from 13 to 136 new words in total. This progress spans varied linguistic categories, including verbs, adjectives, and nouns, signifying substantial vocabulary enrichment. The participants expanded their vocabulary in diverse communicative situations, including travelling, exploring a city, having persuasive conversations, and solving crimes. Furthermore, the research showcased a positive shift in middle-aged adults' motivation, with participants expressing engagement and enthusiasm. This change was attributed to the game's interactivity, contextual vocabulary practice, and an enjoyable learning experience. This not only enriched vocabulary but also positively influenced attitudes and motivation. These findings suggest that video games effectively enhance vocabulary and motivation for middle-aged learners, offering a meaningful learning experience rooted in relatability. It is concluded that video games are effective tools for vocabulary improvement and motivation among adult learners. The findings of this study have important implications for language educators.